Cardiomiopatía dilatada en un cachorro. Reporte de un caso - Tarazona Ch., Sandra L.; Gómez G., Leonardo F.; Orozco P., Sonia C. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary This is a case of a Springer spaniel puppy which presented tachypnea, ascitis, exercise intolerance, mild cyanosis and a poor body condition. At cardiac auscultation a 5/6 mitral murmur was detected that irradiated to both hemithorax. Echocardiography revealed diminished left ventricular contractility, eccentric hypertrophy of the left atrium and ventricle and mitral insufficiency.